Key competencies for digital transformation in workplace - Faina, I.; Almeida, F. (Knowledge, people, and digital transformation: Approaches for a sustainable future, 2020)
There is evidence that artificial intelligence and automation will affect and be present in portions of almost all jobs, either in a greater or lesser degree. Notwithstanding, these digital transformations will eliminate very few jobs and occupations over the next decades. Taking this into account, this research intends to identify which competencies are more valuable for workers who work in a technological workplace, by the employers’ perspective. It means this research will explore, listening to employers’ opinion, which competencies are the ones that make a worker lead and responds positively to a digital implementation in their workplace. Results were gathered through a Delphi study, within a panel of six experts in the human resources for the technological industries field. It is finding that employers consider adaptability and creativity as the most important competencies for technological work. In addition, informatic competencies were less valuable by employers while considering the importance of workers dealing with digital transformations in workplaces.